Mais qui est donc le monstre ? À propos d’agentivité et de responsabilité dans la relation entre l’humain et la machine - Barbara Hof (Cahiers du MIMMOC)
This article addresses the attribution of « agency » to non-human, non-biological actors. Starting from the concept of « agency » developed in Science and Technology Studies (STS), the article contributes to current debates about ethical responsibility. Drawing on Polanyi’s paradox, I argue that the monstrosity of artificial intelligence (AI) is not rooted in machines but is instead primarily conjured by the imagination and interests of humans. Machines can neither develop intrinsic motives nor possess tacit knowledge. Therefore, the article offers a practical as well as a theoretical conclusion : first, humans must always bear responsibility for the hazards and risks of machine « agency », and second, the new challenges posed by machine learning call for further development around the notion of agency.